2006
DOI: 10.1002/pssc.200564132
|View full text |Cite
|
Sign up to set email alerts
|

InAsSb/InGaAs quantum nanostructures on InP (100) substrate: observation of 2.35 µm photoluminescence

Abstract: A theoretical and experimental study of the electronic properties of InAsSb quantum dots (QDs) grown on InP substrate is presented. Unstrained bulk InAsSb presents a direct gap between 0.1 eV to 0.35 eV, suitable for mid infrared emitters (3-5 µm). However, strain and quantum confinement effects may limit the extension of the emission spectrum of these nanostructures towards longer wavelengths. Various combinations of barrier materials are considered in the simulations. 1 Introduction Efficient semiconductor l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…These nanostructures have potential applications in mid-infrared optoelectronic devices. [8][9][10][11][12] It is found that by using different graded approaches the actual Sb composition in InAsSb nanostructures can be changed significantly despite the fact that their nominal Sb mole fraction (averaged over the graded growth) is kept the same, which results in different morphologies for the InAsSb nanostructures. As a result of their composition and morphological changes, photoluminescence from these InAsSb nanostructures shows different polarization and temperature characteristics.…”
mentioning
confidence: 99%
“…These nanostructures have potential applications in mid-infrared optoelectronic devices. [8][9][10][11][12] It is found that by using different graded approaches the actual Sb composition in InAsSb nanostructures can be changed significantly despite the fact that their nominal Sb mole fraction (averaged over the graded growth) is kept the same, which results in different morphologies for the InAsSb nanostructures. As a result of their composition and morphological changes, photoluminescence from these InAsSb nanostructures shows different polarization and temperature characteristics.…”
mentioning
confidence: 99%
“…In the past several years, self-assembled InAsSb nanostructures such as quantum dots ͑QDs͒, quantum dashes ͑QDashes͒, and quantum wires ͑QWRs͒, have attracted much attention due to their potential as midinfrared emitters for applications in military, telecommunications, molecular spectroscopy, biomedical surgery, environmental protection, and manufacturing industry. [1][2][3][4][5] Compared with In͑Ga͒As nanostructures on GaAs or InP substrates, these InAsSb nanostructures have much smaller island sizes ͑ϳ1 -3 nm in height͒ due to the large lattice mismatch between InAsSb and GaAs or InP materials. [5][6][7][8] The large strain and strong spatial confinement ͑induced by the small island height͒ in this material system will have a significant influence on the optical and electronic properties of these InAsSb nanostructures, and thus their device performance.…”
mentioning
confidence: 99%
“…In recent years, InP-based InAsSb nanostructures have attracted considerable attention due to their potential applications as mid-infrared emitters (2-3 µm) [1][2][3][4][5]. Some work has been done on the direct growth of InAsSb nanostructures, where As and Sb atoms are deposited simultaneously with In atoms [5][6][7][8].…”
mentioning
confidence: 99%